A numerical study of air flow in a coaxial pipe - Adi, Surjosatyo; Ani, Farid Nasir (Penerbit UTM Press, 2001)
A simulation study of a cold-flow in coaxial pipes was carried out with varying drivepipe diameter and entrance displacement (?L). The current work has studied the effect of the temperature of the entrance flow inlet with variation of ?L to the entrained flow characteristics. To predict these flow characteristics, a numerical method was employed by the differencing scheme for integrating the continuity equation and energy equation. A k-? turbulent model was used to simulate the turbulent transport quantities. The 2-D flow pattern was created as the result of using Fluent version 4.4 CFD modeling package. Results showed that increasing the air entrained temperature until 600 K would decrease the airflow rate. It was found that the diameter ratio of 2.81 has the highest entrained flow rate